Magnetic Study of a Pentanuclear Co2IIICo3II Cluster with a Bent CoII3 Motif - Lazzarini Behrmann, Irene Constanza (2014)
We have synthesised and structurally characterised a new pentanuclear mixed-valent cobalt cluster of formula [CoII3CoIII2(OH)2(piv)6(L)2(H2O)4] (piv = trimethylacetate, H2L = salicylideneanthranillic acid) from reaction of a dinuclear cobalt pivalate precursor with a Schiff base type ligand under mild reaction conditions. The core structure can be conveniently described as two fused Co3–μ3–OH triangles with a strict unique sharing vertex point. A complete picture of the magnetic behaviour of this compound is presented. Through combined use of susceptibility, magnetisation, and EPR data as well as broken-symmetry DFT calculations, we have supported the magnetic data that show weak and anisotropic exchange interaction between CoII ions affording an Seff = 1/2 ground state that is not completely isolated from the low-lying excited doublets at low temperature. Under the optimum applied field of 2 kOe, a frequency-dependent out-of-phase susceptibility signal can be observed below 4 K. However, no reliable relaxation rates could be extracted due to the narrow temperature range in which this behaviour was observed.